Multicompartment and cross-species monitoring of contaminants of emerging concern in an estuarine habitat. (1st February 2021) - Miller, Thomas H.; Ng, Keng Tiong; Lamphiere, Aaron; Cameron, Tom C.; Bury, Nicolas R.; Barron, Leon P.
Abstract: The fate of many chemicals in the environment, particularly contaminants of emerging concern (CEC), have been characterised to a limited extent with a major focus on occurrence in water. This study presents the characterisation, distribution and fate of multiple chemicals including pharmaceuticals, recreational drugs and pesticides in surface water, sediment and fauna representing different food web endpoints in a typical UK estuary (River Colne, Essex, UK). A comparison of contaminant occurrence across different benthic macroinvertebrates was made at three sites and included two amphipods ( Gammarus pulex & Crangon crangon ), a polychaete worm ( Hediste diversicolor ) and a gastropod ( Peringia ulvae ). Overall, multiple contaminants were determined in all compartments and ranged from; <LOQ – 386 ng L −1 in surface water (n = 59 compounds), <LOQ – 146 ng g −1 in sediment (n = 39 compounds) and <LOQ – 91 ng g −1 biota (n = 33 compounds). H. diversicolor and P. ulvae (sediment dwellers) showed greater chemical body burden compared with the two swimming amphipod species sampled (up to 2.5 - 4-fold). The most frequently determined compounds in biota (100%, n = 36 samples) included; cocaine, benzyoylecgonine, carbamazepine, sertraline and diuron. Whilst some of the highest concentrations found were in species H. diverscolor and P. ulvae for psychoactive pharmaceuticals including citalopram (91 ng g −1 ), sertraline (69 ng g −1 ), haloperidol (66 ng g −1 ) and the neonicotinoid, imidacloprid (33 ng g −1 ) Sediment was noted as an important exposure route for these benthic dwelling organisms and will be critical to monitor in future studies. Overall, the analysis of multiple species and compartments demonstrates the importance of including a range of exposure pathways in order to appropriately assess chemical fates and associated risks in the aquatic environment. Graphical abstract: Image 1 Highlights: Multi-compartmental monitoring across three sites of an estuarine habitat is presented. The most impacted site was next to a WWTP discharge point. Emerging contaminants across four different macroinvertebrates reached up to 91 ng g −1 . Infaunal species showed greater accumulation of contaminants than epibenthic organisms. A high proportion of contaminants determined in biota were psychoactive drugs. Abstract : Multi-class contaminants of emerging concern were determined across surface water, sediment and macroinvertebrate species demonstrating widespread exposure in the aquatic environment.